The Dream merchants ; Insight of the sightless ; Ang manager Nakaw koryente ; Of spirit, sorcerers ; A wake in Batac [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Discusses the problems of illegal recruitment agencies that victimize those who are in dire need of work specifically those who would want to work abroad; the thoughts, feelings and dreams of the blind ; a look at managers of artists; a report on poewr pilferage--stealing of electricity through the use of jumpers, use of tampered meters, and illegal connections; the Filipino belief in the supernatural ; and the request of the Marcos family and followers that his remains be burried in the Philippines.